2016
DOI: 10.18632/oncotarget.13046
|View full text |Cite
|
Sign up to set email alerts
|

Multiple primary lung cancer displaying different EGFR and PTEN molecular profiles

Abstract: We present a case of multiple primary lung cancer(MPLC) displaying heterogeneous EGFR and PTEN molecular profiles. Considering the physical condition of patients, the patient underwent surgical resection of the right lung lesion displaying gefitinib-insensitive and continued gefitinib treatment for the gefitinib-sensitive lesions in the left lung. As far as we know, this is the first report documenting a case of an integrated therapy strategy using surgical resection with gefitinib treatment for MPLC displayin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“… 9 In 35%~60% of MPLC patients, TP53 gene mutations can be used to determine whether the clonal origin of each lesion is the same. 10 In this case, TP53 mutations were different in the two lesions, which verified their different sources. A genomic analysis based on NENs patients in China showed that co‐mutations of TP53 and RB1were detected in 95% of SCLCs.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“… 9 In 35%~60% of MPLC patients, TP53 gene mutations can be used to determine whether the clonal origin of each lesion is the same. 10 In this case, TP53 mutations were different in the two lesions, which verified their different sources. A genomic analysis based on NENs patients in China showed that co‐mutations of TP53 and RB1were detected in 95% of SCLCs.…”
Section: Discussionsupporting
confidence: 55%
“…Mutations in the tumor protein p53 (TP53) gene and RB transcriptional corepressor 1 (RB1) gene are common in high‐grade lung neuroendocrine tumors 9 . In 35%~60% of MPLC patients, TP53 gene mutations can be used to determine whether the clonal origin of each lesion is the same 10 . In this case, TP53 mutations were different in the two lesions, which verified their different sources.…”
Section: Discussionmentioning
confidence: 90%
“…While the left lobe lesions responded to TKI, the poorly differentiated lesion of the right lobe progressed. After resection of the right lobe, the tissue was subjected to mutation analysis, which revealed a PTEN mutation, but no EGFR mutations [94]. PTEN proficient HCC827 cells with the sensitizing to-TKI-therapy EGFR mutation showed high sensitivity to gefitinib.…”
Section: Pten-mediated Resistance To Targeted Therapymentioning
confidence: 99%
“…recommend extensive molecular profiling in cases with multiple lung cancers, as it might clarify the association between the lung lesions found . Several investigators have reported the utility of molecular biological analysis for diagnosis and treatment in multiple primary cancers, not only in lung cancer but also breast, gastric, hepatocellular, renal, and colorectal cancers . Thus, molecular biological analysis is necessary when multiple cancers of the same histotype are identified in the same tissue where there are multiple primary tumors.…”
Section: Discussionmentioning
confidence: 99%